Український метанаратив доби Модерну: семантика темпоральності - Колесников, К. (Інститут історії України НАН України, 2008)
The given article is dedicated to the description and analysis of changes of evolution of the metanarrative of Ukrainian historical discourse at different stages of Modernity (New Time). The author esteems changes of the forms (images) historical metanarrative (according to John Stephens it “is a global or totalizing cultural narrative schema which orders and explains knowledge and experience”) – complex of representations about the Ukrainian history as continuous and series on all the extent from an antiquity up to a modernity.